Biodegradable ionic liquids in service of biomass upgrade - Piedade, Patrícia J. (2022)
ABSTRACT: This work presents an up-to-date overview of the use of biodegradable ionic liquids in the conversion of biomass in the context of biorefineries. Special attention is given to works in which biodegradability potentiates advanced application of ionic liquids in terms of process intensification for deployment of technologies towards bioenergy carriers or bioderived valueadded products.